Experiences of Early Childhood Education Services in a Migrant Community - Puri, Vardhna; Bhargava, Vinita; Sharma, Bhanumathi (JOURNAL OF INDIAN EDUCATION, 2020)
Migration is a crucial feature of urban areas. People have been migrating for varied reasons, to improve quality of living being crucial reason. It affects lives of people in both positive and negative ways. Migration adds to the vulnerability of poorer families. This study is aimed to understand lives of women and children in migrant families. A locality in Delhi with high migrant population was selected. The locality was an informal settlement with a dense population. 100 families were contacted and 20 families were selected for indepth understanding. Primarily qualitative methods were used for the study. The role of early childhood care workers, primarily aanganwadi centres was highlighted. They had an important role to play in the lives of children and their families.